Food, Inc. 2 [videorecording (DVD)] - Pollan, Michael; Schlosser, Eric; Reyes-Chavez, Gerardo (Magnolia Home Entertainment, 2024)
Robert Kenner and Melissa Robledo team up with authors Michael Pollan and Eric Schlosser to examine the modern food industry's efficiency and vulnerabilities. -- Provided by publisher.